2022
DOI: 10.21203/rs.3.rs-1262325/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association Between Perceived Stress, Loneliness and Sleep Disorders Among Breast Cancer Patients: the Moderating Roles of Resilience

Abstract: Purpose: Sleep disorders are prevalent and often neglected among breast cancer patients. This study aimed to identify the association among perceived stress, loneliness, resilience and sleep disorders, and to further explore whether resilience could be a moderator in the association between perceived stress, loneliness and sleep disorders among Chinese female breast cancer patients.Methods: A cross-sectional study was conducted at a tertiary hospital in Anshan, China from October 2019 to October 2020. 492 vali… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
2
1
0
Order By: Relevance
“…While the PSS does not have a clinically meaningful cutoff score, our patients reported scores that were similar to those reported by oncology patients receiving radiation therapy (Ravindran et al., 2019) and cancer survivors who underwent chemotherapy within the previous year (Zhang et al., 2022). In addition, our findings are consistent with previous studies of patients with digestive (Lv, Zhao, Xie, et al., 2022) and breast (Ban Y, 2022) cancer that found significant positive associations between sleep disturbance and perceived global stress.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…While the PSS does not have a clinically meaningful cutoff score, our patients reported scores that were similar to those reported by oncology patients receiving radiation therapy (Ravindran et al., 2019) and cancer survivors who underwent chemotherapy within the previous year (Zhang et al., 2022). In addition, our findings are consistent with previous studies of patients with digestive (Lv, Zhao, Xie, et al., 2022) and breast (Ban Y, 2022) cancer that found significant positive associations between sleep disturbance and perceived global stress.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, our findings are consistent with previous studies of patients with digestive (Lv, Zhao, Xie, et al, 2022) and breast (Ban Y, 2022) cancer that found significant positive associations between sleep disturbance and perceived global stress.…”
Section: Global Stresssupporting
confidence: 93%
See 1 more Smart Citation